2017
DOI: 10.3389/fchem.2017.00094
|View full text |Cite
|
Sign up to set email alerts
|

How Are Substrate Binding and Catalysis Affected by Mutating Glu127 and Arg161 in Prolyl-4-hydroxylase? A QM/MM and MD Study

Abstract: Prolyl-4-hydroxylase is a vital enzyme for human physiology involved in the biosynthesis of 4-hydroxyproline, an essential component for collagen formation. The enzyme performs a unique stereo- and regioselective hydroxylation at the C4 position of proline despite the fact that the C5 hydrogen atoms should be thermodynamically easier to abstract. To gain insight into the mechanism and find the origin of this regioselectivity, we have done a quantum mechanics/molecular mechanics (QM/MM) study on wildtype and mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 100 publications
2
12
0
Order By: Relevance
“…Thus, due to tight substrate binding and positioning, the hydrogen atom abstraction will be selective from only one of the two hydrogen atoms from the ω-1 position of the substrate. Hence the hydrogen atom abstraction will guide the enantioselectivity as seen before on related enzymes (Karamzadeh et al, 2010 ; Pratter et al, 2013 ; Timmins and de Visser, 2017 ; Timmins et al, 2017 ). Nevertheless, in HctB the first halogenation of substrate is followed by a second halogen transfer through the binding of another molecule of O 2 and Cl − to repeat the cycle and the formation of the dihalogenated product.…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…Thus, due to tight substrate binding and positioning, the hydrogen atom abstraction will be selective from only one of the two hydrogen atoms from the ω-1 position of the substrate. Hence the hydrogen atom abstraction will guide the enantioselectivity as seen before on related enzymes (Karamzadeh et al, 2010 ; Pratter et al, 2013 ; Timmins and de Visser, 2017 ; Timmins et al, 2017 ). Nevertheless, in HctB the first halogenation of substrate is followed by a second halogen transfer through the binding of another molecule of O 2 and Cl − to repeat the cycle and the formation of the dihalogenated product.…”
Section: Resultsmentioning
confidence: 84%
“…Furthermore, the methods reproduced experimental product distributions of bifurcation processes well (Ji et al, 2015 ; Kaczmarek et al, 2018 ). Finally, for the nonheme iron dioxygenase prolyl-4-hydroxylase six hydrogen atom abstraction barriers from substrate were investigated and the QM/MM predicted the correct regioselectivity and therefore the methods are expected to predict regio- and chemoselectivities well (Karamzadeh et al, 2010 ; Pratter et al, 2013 ; Timmins and de Visser, 2017 ; Timmins et al, 2017 ).…”
Section: Resultsmentioning
confidence: 99%
“…46,47 Thereafter, dioxygen was placed in a position near the active site Asn residues. A standard procedure was followed for the subsequent set-up of the system, as described in more detail elsewhere, [38][39][40][48][49][50][51] and briefly summarized here. The enzyme model was set up using procedures proposed by Thiel et al 52,53 The substrate bound enzyme structure with dioxygen bound was protonated to pH 7 with the PROPKA method using the PDB2PQR web service, 54 whereby all Glu and Asp side chains were deprotonated and all Arg and Lys side chains protonated.…”
Section: Methodsmentioning
confidence: 99%
“…Specifically, most NHFeHas require their substrate be tethered to a phosphopantetheine arm (PPT) associated with an acyl-carrier protein (ACP) [136,137], whereas the hydroxylases tend to have free substrates, although they are often bound tightly in a substrate binding pocket. For example, the prolyl-4-hydroxylase from Clamydomonas reinhardtii tightly binds the substrate through selective hydrogen bonding involving amino acids in two loops (β 3 -β 4 loop and the β II -β III ) which cover the substrate [138,139]. The only halogenase that forms an exception to this rule appears to be WelO5, whose recent discovery revealed that it did not require a PPT arm to deliver its substrate into the active site.…”
Section: Nonheme Iron/α-ketoglutarate Halogenasesmentioning
confidence: 99%
“…As mentioned above, the catalytic cycle of NHFeHys and NHFeHas is largely similar; however, post-hydrogen atom abstraction from the substrate, the systems bifurcate. In the NHFeHys, a hydroxyl radical rebounds, forming the hydroxylated product [138,139,148,149], in contrast to NHFeHas, whereby, a chloride radical relay gives the halogenated product. The factors related to bifurcation have been the subject of study for many years, ever since the discovery of NHFeHas, and has created a number of controversies and mechanistic possibilities.…”
Section: Nonheme Iron/α-ketoglutarate Halogenasesmentioning
confidence: 99%